PENGGUNAAN MEDIA KARTU UNTUK MENINGKATKAN MINAT BELAJAR BAHASA ARAB SISWA KELAS VII MTsN TANJUNGANOM NGANJUK - Asmaul Husna; Inchinia Angger Rowin (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
Media is one component of communication, namely as a message from the communicator to the communicant. One of the main functions of learning media is as a teaching aid that also influences the climate, conditions and learning environment that are arranged and created by the teacher. While the word card is a word card inscribed with words that are used as media or tools in the learning process to improve students' abilities. In learning Arabic, media can be used as an effort to increase students' motivation, interest, arouse enthusiasm, and turn on lessons that allow for active interaction and participation. Seeing the existing facilities at MTsN Tanjunganom, there is still a lack of media, especially the language laboratory, so the teacher tries to use other media, namely visual media in the form of cards in Arabic learning. This study wanted to find out how the implementation and effectiveness of learning using visual media in the form of cards. The type of research used is Classroom Action Research. The type of data obtained from this research is qualitative. Qualitative data obtained from documentation, observation and interviews. while the data sources of this research are students of class VII MTsN Tanjunganom Nganjuk. Based on the description above, the researcher can conclude that, it can be seen from the students' understanding or mastery of the Arabic language material that has been delivered through learning trials using card media. By using this card media, students are invited to really master the material, both in theory and practice. Because this card media puts forward a lot of practice rather than just delivering material. With the use of this card media, it is very effective to increase students' interest in learning Arabic, especially class VII MTsN Tanjunganom Nganjuk.